Optimal design of cold roll formed steel channel sections under bending considering both geometry and cold work effects. (December 2020) - Qadir, S.J.; Nguyen, V.B.; Hajirasouliha, I.; Cartwright, B.; English, M.A.
Abstract: Optimal design of a structural member is a design process of selecting alternative forms to obtain its maximum strength while maintaining the same weight, leading to the most economical and efficient structure. Amongst steel structures, cold rolled steel ones can effectively gain this requirement as they are thin-walled structures that offer the high ratio of strength over weight. However, the design is very challenging as these members are prone to buckling and failure at low loads. In this paper, the buckling and ultimate strength of cold rolled channel sections was studied using numerical modelling. In order to improve the section strength, the development of various alternative cold rolled formed sections included additional bends such as intermediate stiffeners. The section strength was optimised through a practical approach which altered the stiffener's position and shape and searched for maximum buckling and ultimate strength under bending. In this approach, a nonlinear Finite Element model was first developed for an industrial channel beam subjected to four-point bending tests and this model was validated against experimental test data. The verified model was then used to conduct a parametric study in which the effects of a stiffener's properties on the section strength including its position, shape, size and material properties by the cold work at bends were investigated in detail. Several different cold rolled channel sections having intermediate stiffeners at web and flanges with and without the cold work effect on material properties at the stiffener's bends were considered for this investigation. In addition, a design method, the Direct Strength Method (DSM), was utilised to take into account the effects of a stiffener's properties on the section strength and results were compared with the Finite Element modelling results. It was found that some significant improvements were obtained for the section strength of the optimised sections in comparison to the original sections. An optimal shape for the channel section with maximum ultimate strength in distortional buckling could be obtained with both the stiffeners' position, shape, size and quantity, and the cold work effect. The cold work effect was found most significant in the cases of changing the width of the web stiffeners and the position of the flange stiffeners. It also revealed that, the currently available DSM beam design curve for distortional buckling provided good agreement in predicting buckling load and ultimate strength capacity for most of the considered sections with and without the cold work effect included; however, the DSM provided overestimate results compared to the Finite Element model results in the sections with web intermediate stiffeners, in particular, when the tip of web intermediate stiffener moved away from the web-flange junction in the horizontal direction. Highlights: FE simulations of channel and zed beams were established and compared with DSM and tests. FE models and DSM accounted for material properties at section bends due to cold work. Effects of both the stiffeners' geometry and cold work on strength of channels was investigated by FE models and DSM. An optimal design of channels considering stiffeners' geometry and cold work was proposed.